A COMPARATIVE STUDY OF PERINEAL WOUND HEALING RATES IN POSTPARTUM WOMEN CONSUMING SNAKEHEAD AND MACKAREL TUNA FISH - Dwi Kurnia Purnama Sari; Nur Cholila (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Ideally, perineal wounds take 6-7 days to heal. The wound healing process requires protein that can be obtained from fish as a basic nutrient for cell formation. The availability of fish in Indonesia is very high, but the national fish consumption rate is low. The purpose of this study was to analyze the difference in the speed of perineal wound healing in postpartum mothers with protein intake from snakehead fish and mackarel tuna fish. Method: This study used a quasi-experimental design with a post-test only control group design approach. The number of samples used was 48 respondents who were selected using simple random sampling and divided into three groups. Result: The results of the Kruskal Wallis analysis showed a P value of 0.036, so it can be concluded that there is at least an effect of providing intervention on perineal wound healing. The highest wound healing ranking was in the snakehead fish group with a value of 20.45, then the mackarel tuna fish group 16.45 and the control group 9.60. Conclusion : So mothers who have perineal stitches are advised to increase their protein consumption from either snakehead fish or mackarel tuna fish as an alternative to accelerate the perineal wound healing process.